Case Report: A Rare Case of Coexisting of Autoimmune Polyglandular Syndrome Type 3 and Isolated Gonadotropin-Releasing Hormone Deficiency - Jiang, Qiuhui; Wu, Ting; Zhang, Yuxian; Wang, Shunhua; Wang, Liying; Su, Weijuan; Lin, Mingzhu; Li, Xuejun (Frontiers in Immunology, 2021)
APS (autoimmune polyglandular syndrome) is defined as the coexistence of at least two kinds of endocrine autoimmune diseases. APS type 3 comprises autoimmune thyroid diseases and other autoimmune diseases but does not involve autoimmune Addison’s disease. So far, APS-3 combined with isolated gonadotropin-releasing hormone (GnRH) reduction caused by the suspected autoimmune hypothalamic disease has not been reported. We recently received a 43-year-old woman with a one-year history of Graves’ disease (GD) and a four-month history of type 1 diabetes presented with hyperthyroidism and hyperglycemia. After the GnRH stimulation test, she was diagnosed with secondary amenorrhea attributed to suspected autoimmune Hypothalamitis and APS type 3 associated with Graves’ disease and Latent Autoimmune Diabetes (LADA). According to this case, the hypothalamus cannot be spared from the general autoimmune process. It is recommended to carry out the GnRH stimulation test when encountering APS patients combined with secondary amenorrhea.